2022
DOI: 10.1002/cam4.5170
|View full text |Cite
|
Sign up to set email alerts
|

COL3A1: Potential prognostic predictor for head and neck cancer based on immune‐microenvironment alternative splicing

Abstract: We aimed to identify a novel prognostic biomarker for head and neck squamous cell carcinoma (HNSCC) based on tumor immunology‐related alternative splicing (AS). Data for 502 HNSCC and 44 normal samples were obtained from the TCGA database and used to establish an AS‐related risk model through univariate, least absolute shrinkage, and selection operator Cox regression analyses. Fresh HNSCC and normal oral tissues were surgically obtained from 44 HNSCC patients. Western blotting and quantitative reverse transcri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…At present, there are few related studies on the role of COL3A1 in HNSCC. One study reported that COL3A1 has a good role in evaluating the immune cell infiltration, immune activity and gene expression of immune checkpoint of HNSCC lesions (28). At the same time, the head and neck are rich in connective tissue, so it is also of anatomical significance to study the role of COL3A1 in HNSCC.…”
Section: What Is the Implication And What Should Change Now?mentioning
confidence: 99%
“…At present, there are few related studies on the role of COL3A1 in HNSCC. One study reported that COL3A1 has a good role in evaluating the immune cell infiltration, immune activity and gene expression of immune checkpoint of HNSCC lesions (28). At the same time, the head and neck are rich in connective tissue, so it is also of anatomical significance to study the role of COL3A1 in HNSCC.…”
Section: What Is the Implication And What Should Change Now?mentioning
confidence: 99%
“…Immune cells can intimately interact with stromal cells and further impact tumor progression, invasion, and metastasis. A study showed that patients with head and neck squamous cell carcinoma (HNSCC) with increased COL3A1 levels also had a higher level of resting CD4 + T cells and resting NK cells [ 35 ]. The expression of COL3A1 was associated with the increase of IL-1β in osteoarthritis and was also linked to immune cell infiltration [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“… 7 COL3A1 is also identified as a promising independent predictor for prognosis of head and neck cancer and colorectal cancer. 8 , 9 Abnormal expression of COL3A1 mediated by RNF185 exhibits a potent regulatory activity in the metastatic potential of prostate cancer. 10 Moreover, in triple negative breast cancer, knocking down COL3A1 plays a repressive role in cancer cell growth and metastasis depending on PD-L1 reduction.…”
Section: Introductionmentioning
confidence: 99%